Pendampingan Layanan Administrasi Kependudukan Dalam Rangka Optimalisasi Program Kawasan Lingkungan Sadar Administrasi Kependudukan (KALIMASADA) Pada Kelurahan Dukuh Sutorejo - M. Khoirur Rifqi; Maharani Ikaningtyas (Pusat Riset dan Inovasi Nasional, 2023)
Surabaya city is one of the areas in Indonesia which has a large population. The large number of residents moving of Surabaya City has prompted Dinas Kependudukan dan Pencatatan Sipil as a Regional Apparatus in charge of population administration and civil registration in the Surabaya to improve the management of the population administration for its citizens. The purpose of the community service carried out is to help the Surabaya city in improving the quality of Population Administration service assistance and increasing citizen awareness of population Administration arrangements so that later a conscious community environment area can be realized it. and get the maximum Kalimasada data. The results that have been achieved that the writer can complete data on Kalimasada RW 07 Dukuh Sutorejo sub-district and provide understanding to residents about Population Administration and be able to create alternatives that can make it easier for residents to manage it.